2018
DOI: 10.15403/jgld.2014.1121.274.tlr
|View full text |Cite
|
Sign up to set email alerts
|

TLR1 and PRKAA1 Gene Polymorphisms in the Development of Atrophic Gastritis and Gastric Cancer

Abstract: Background & Aims: Previous genome-wide association studies showed that genetic polymorphisms in toll-like receptor 1 (TLR1) and protein kinase AMP-activated alpha 1 catalytic subunit (PRKAA1) genes were associated with gastric cancer (GC) or increased Helicobacter pylori (H. pylori) infection susceptibility. The aim of this study was to evaluate the association between TLR1 and PRKAA1 genes polymorphisms and H.pylori infection, atrophic gastritis (AG) or GC in the European population.Methods: Single-nucle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 24 publications
(16 citation statements)
references
References 44 publications
0
15
0
1
Order By: Relevance
“…19 A study from Europe with mixed Caucasian populations obtained negative results for the association between this SNP and GC risk. 20 However, a recent meta-analysis combining all included studies showed no relationship between this SNP and GC risk in Asians. 21 breast cancer risk.…”
Section: Discussionmentioning
confidence: 98%
“…19 A study from Europe with mixed Caucasian populations obtained negative results for the association between this SNP and GC risk. 20 However, a recent meta-analysis combining all included studies showed no relationship between this SNP and GC risk in Asians. 21 breast cancer risk.…”
Section: Discussionmentioning
confidence: 98%
“…Among these genes, PRKAA1, SQSTM1, and IL6 are closely related to cell proliferation and apoptosis. PRKAA1 encodes for the adenosine monophosphate activated protein kinase (AMPK), which regulates tumor growth and proliferation by regulating energy metabolism ( Dargiene et al, 2018 ). He et al pointed out that LINC00473 regulated ESCC development through the miR-497-5p/PRKAA1 axis ( He, 2019 ).…”
Section: Discussionmentioning
confidence: 99%
“…Various gene polymorphisms have been extensively studied as potential biomarkers for disease prediction, including premalignant gastric conditions and gastric cancer [ 33 , 34 , 35 , 36 , 37 , 38 ]. The most recent advancements in genomics enable scientists to identify single nucleotide polymorphisms (SNPs), which are the most frequent type of genetic variations in humans [ 39 , 40 ].…”
Section: Genetic Variations In Immentioning
confidence: 99%